Análise da evolução das características organizacionais das empresas de construção face às variações do ambiente econômico entre 2010 e 2016 - Teixeira, Felipe (2017)
The way a company organizes itself is directly related to its efficiency and capacity of remaining competitive during periods of economic crisis. In the face of the importance of organizational structure in business performance, this study aims to analyze the evolution of the organizational characteristics of construction companies with regard to the economic environment variations that took place between 2010 and 2016. The method for conducting this study was the Survey, allowing primary data to be obtained in a systematized way. Four data collections were performed by the "Núcleo de Inovação de Gestão da Construção" (Nucleus of Innovation in Construction Management) - NIGEC, from the Universidade Tecnológica Federal do Paraná, in the years 2010, 2012, 2014 and 2016. In total, 362 surveys were applied to civil construction companies that operate in Curitiba and region. The data was analyzed by means of descriptive statistics, non-parametric inferential analysis, and discriminant analysis. The results show, in general, that those companies researched display consolidated characteristics, remaining unchanged in spite of the large economic variations during the period. Among the characteristics, the ones that stand out are the predominantly centralized structures, the ongoing concern in regards to cost reduction, and activity in a market classified as unpredictable. Other characteristics are directly affected by economic variations. Especially in such times of economic crisis, companies tend to increase the levels of training, to invest in technology and equipment, and to encourage the autonomy of its employees. Thus, in general, the organizational characteristics show a sector with a traditional and outdated management, but that in moments of hardship seeks modernization alternatives in order to overcome deficiencies and increase competitiveness.